Urgensi Pembaharuan Kitab Undang-Undang Hukum Perdata di Indonesia - Gerhard Mangara; Tazqia Aulia Al-Djufri (Jurnal Hukum Lex Generalis, 2022)
The Indonesian Civil Code still refers to Burgerlijk Wetboek (BW), a legacy from the Dutch colonial era which inaugurated from Staatsblad 1847 No. 23. Since then, BW has become the main reference for civil law in Indonesia and remains in effect even after Indonesia’s independence. Based on Article 1 Transitional Rules of Indonesian Constitution. However, until now there has not been a new Civil Code Act as a substitute for the Dutch East Indies Civil Code which has been ratified. As the main legal basis, there are several problems such as the lack of clarity regarding the status of the Civil Code, difficulties in translation, and several articles in it that are not in accordance with the times. This article argues that the renewal of the Civil Code in Indonesia is an urgent matter by combing through articles that are still relevant and in accordance with the times.